Structural and enzymatic characterization of a purified prohormone-processing enzyme: secreted, soluble Kex2 protease. - Brenner, C (1992)
The prohormone-processing Kex2 protease of the budding yeast Saccharomyces cerevisiae can be converted from an intracellular membrane protein to a soluble, secreted, and active form by deletion of the transmembrane domain and C-terminal tail. One such molecule was purified to near homogeneity from the culture medium of an overexpressing yeast strain. Amino acid sequence analysis revealed that the N terminus of mature Kex2 protease is created by a potentially autoproteolytic cleavage at Lys108-Arg109, prior to the domain homologous to subtilisin, followed by trimming of Leu-Pro and Val-Pro dipeptides by the Ste13 dipeptidyl aminopeptidase. Kinetic parameters were examined using fluorogenic peptidyl-methylcoumarin amide substrates. Initial burst titration indicated that the preparation was entirely active. Measurements of dependence of activity on pH yielded a simple curve suggesting titration of a single ionizable group. Activity was half-maximal at pH 5.7 and nearly constant from pH 6.5 to 9.5. Discrimination between substrates was as great as 360-fold in Km and 130-fold in kcat. Substrates with a Lys-Arg dipeptide preceding the cleaved bond were preferred, having kcat/Km values up to 1.1 x 10(7) sec-1.M-1. The enzyme cleaved substrates having Arg-Arg, Pro-Arg, Ala-Arg, and Thr-Arg with increased Km but with unchanged kcat. In contrast, the enzyme displayed a dramatically lower kcat for a Lys-Lys substrate with a smaller increase in Km. Thus the two residues preceding the cleaved bond may play distinct roles in the selectivity of binding and cleavage of prohormone substrates.